Cultural Competence and Humility in Infectious Diseases Clinical Practice and Research. (14th September 2020) - Hussen, Sophia A; Kuppalli, Krutika; Castillo-Mancilla, José; Bedimo, Roger; Fadul, Nada; Ofotokun, Ighovwerha
Abstract: Infectious diseases as a specialty is tilted toward social justice, and practitioners are frequently on the front lines of the battle against health inequity in practices that are diverse and sometimes cross international borders. Whether caring for patients living with the human immunodeficiency virus, tuberculosis, or Ebola, infectious diseases practitioners often interact with those at the margins of societies (eg, racial/ethnic/sexual/gender minorities), who disproportionately bear the brunt of these conditions. Therefore, cultural barriers between providers and patients are often salient in the infectious diseases context. In this article, we discuss cultural competence broadly, to include not only the knowledge and the skills needed at both the organizational and the individual levels to provide culturally appropriate care, but also to include "cultural humility"—a lifelong process of learning, self-reflection, and self-critique. To enhance the quality and the impact of our practices, we must prioritize cultural competence and humility and be mindful of the role of culture in the patient-provider-system interactions, in our larger healthcare systems, and in our research agendas and workforce development.